Assessment of nutritional status of elderly individuals: a Mini-Nutritional Assessment - Sökülmez Kaya, Pınar (Progress in Nutrition, 2015)
Aim: The study was designed and conducted in order to identify the nutrient consumption of the elderly individuals aged 65 years and over living at home or at a nursing home in Samsun City using the MNA test. Materials and Methods: A total of 182 elderly people aged 65 years and over participated in the study. 82 of them were staying at a nursing home and 100 were living at their own home. The study used a questionnaire including socio-demographic characteristics, the Mini-Nutritional Assessment (MNA), and the records of nutrient consumption. Anthropometric measurements were also taken. The data collected by interview method was analyzed using SPSS Version 13.5. The mean and ± SD were expressed as continuous variables, and the number and the percentage as categorical variables. The data was compared using Student’s t test, Crosstabs chi-square test and Fisher’s exact chi-square test. In all tests, p